2019
DOI: 10.1186/s13063-019-3299-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving primary care Access in Context and Theory (I-ACT trial): a theory-informed randomised cluster feasibility trial using a realist perspective

Abstract: Background Primary care access can be challenging for older, rural, socio-economically disadvantaged populations. Here we report the I-ACT cluster feasibility trial which aims to assess the feasibility of trial design and context-sensitive intervention to improve primary care access for this group and so expand existing theory. Methods Four general practices were recruited; three randomised to intervention and one to usual care. Intervention practices received £1500, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This inaccessibility to transportation prevented many older adults in rural communities from accessing PHC services. Similarly, Ford et al (2019) found that the transportation costs vs. transportation access were more of a barrier faced by older adults to accessing PHC services. Transportation costs range from the lack of funds to purchase and maintain a vehicle, or service a taxi transportation service (Ford et al, 2019).…”
Section: Virtual Carementioning
confidence: 98%
See 4 more Smart Citations
“…This inaccessibility to transportation prevented many older adults in rural communities from accessing PHC services. Similarly, Ford et al (2019) found that the transportation costs vs. transportation access were more of a barrier faced by older adults to accessing PHC services. Transportation costs range from the lack of funds to purchase and maintain a vehicle, or service a taxi transportation service (Ford et al, 2019).…”
Section: Virtual Carementioning
confidence: 98%
“…Two articles were published in Australia, two in the United Kingdom, one in South Africa, and one included the countries Canada, the Netherlands, the United States, the United Kingdom, Slovenia, Guam, and To effectively reduce barriers to older adults' access of PHC services in rural communities, nurse practitioners working in rural communities must recognize these barriers. In the literature, sixteen of the eighteen articles discussed barriers to access of PHC services (Batsis et al, 2019;Bresick et al, 2016;Clare, 2019;Dolovich et al, 2019;Ford et al, 2018Ford et al, , 2019Heale et al, 2018;Hewitt et al, 2019;Hungerford et al, 2016;Hunter et al, 2016;Prasad et al, 2014;Ross et al, 2016;Shah et al, 2017Shah et al, , 2019Wakerman et al, 2008;Weil et al, 2018).…”
Section: Chapter Iv: Findingsmentioning
confidence: 99%
See 3 more Smart Citations